PERANCANGAN STADION SEPAK BOLA DI KOTA DEPOK DENGAN KONSEP STARFRUIT SEBAGAI LAND MARK KAWASAN - YOGANA DWI NAMARA; ATIE ERNAWATI (Faktor Exacta, 2013)
The design of a standard integrated national football stadium complete with lodging athletes and sports stadium to support the development of sport in Depok was started from an idea of the development of sports facilities that can be used as Depok community pride, for it is the presence of Depok City Icons are the star fruit concept development in the design of the stadium resembles a typical star fruit Depok both the interior and exterior of the main building and ancillary buildings. It is expected by Starfruit concepts as landmarks in Depok area can be realized so that residents can be proud of Depok and easily recognized by other regions. Keyword: stadium, football, Starfruit, landmark, area.